1984
DOI: 10.1038/clpt.1984.130
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous modeling of bopindolol kinetics and dynamics

Abstract: Bopindolol has beta-blocking effects for 96 hr despite a 4-hr t1/2. To investigate the concentration-effect relationship after single and repeated doses. 2-mg oral doses were given once and then daily for 13 days to six healthy subjects. In plasma, no unchanged drug, only the hydrolysis product of bopindolol (referred to as bopindolol concentration) was detectable or could be measured up to 24 hr. Chemical assay by HPLC and determination of total active beta-adrenoceptor blocking material by radioreceptor assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

1985
1985
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 0 publications
2
18
0
2
Order By: Relevance
“…This has been confirmed in a pharmacokinetic and pharmacodynamic steady state study by Platzer et al (1984) who, during treatment for 2 weeks, found no evidence for a cumulation of either the plasma levels of hydrolysed bopindolol or of the pharmacodynamic effect measured by the reduction of exerciseinduced tachycardia.…”
Section: Resultssupporting
confidence: 54%
“…This has been confirmed in a pharmacokinetic and pharmacodynamic steady state study by Platzer et al (1984) who, during treatment for 2 weeks, found no evidence for a cumulation of either the plasma levels of hydrolysed bopindolol or of the pharmacodynamic effect measured by the reduction of exerciseinduced tachycardia.…”
Section: Resultssupporting
confidence: 54%
“…Several previous reports have indicated (1) the slowly reversible nature of binding of bopindolol to receptors [10]; (2) the presence of active metabolites [11]; (3) the shallow slope of the plasma concentration-effect relationship [12,13], and (4) the small dissociation Hosohata/Hattori/Shen/Okuyama/ Kaneko/Ohnuki/Suzuki/Nagatomo constant of the drug-receptor complex [14]. Our previous study [2] also showed a slow dissociation of bopindolol and metabolite 18-502 from ß-ARs in the rat and guinea pig heart using pharmacological methods and the radioligand-binding assay.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that bopindolol possesses long-acting ß-blocking action with high affinity and partial agonist activity to the ß-ARs in both healthy volunteers and animal models [9,11,13,14], suggesting that less frequent administration may be necessary than with most other ß-blockers [6,7,11]. It is well known that one active metabolite (18-502) also has strong ß-blocking action, suggesting that this metabolite also contributes to the long-lasting effects of bopindolol [2].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies in healthy volunteers have shown that beta-blockade is almost maximal following single oral doses of 2 mg and that, with this dose, about 50% of the maximal achieved effect is still present 24 h after administration [2,3]. It has also been shown [4] that the results of single-dose studies are predictive for the pharmacody namic response to exercise after multiple doses. Since the therapeutic effect of betaadrenoceptor blocking drugs in the treat ment of angina pectoris is primarily due to the reduction of the heart rate and blood pressure response to stress, it seemed likely that the maximum clinical effect of bopindo lol would be achieved with once-daily doses of 2 mg in such patients.…”
Section: Introductionmentioning
confidence: 89%